Contribution of community health workers to primary health care performance in brazil? - Hugo a Rocha (2020)
OBJECTIVE: To associate the strength of community health workers interventions with primary health care strategies for women’s and children’s health, diabetes, and hypertension.METHODS: This is a cross-sectional study assessing 29,778 family health teams working in primary health care in Brazil in 2014. The association between community health workers activity levels and primary health care facilities was analyzed using multiple logistic regression.RESULTS: We found higher levels of community health workers activities strongly associated with primary health care practices (OR = 6.88) for those activities targeting hypertension management, followed by children’s health (OR = 6.56), and women’s health (OR = 6.21).CONCLUSIONS: At a time when Brazil discusses whether community health workers should or should not remain in the same scale-up and skill level as they currently are, our results reinforce the importance of these workers for the care model advocated by the Brazilian Unified Health System